Development Of Life Skill Through School Sport Activities - Nur Mahfuzah Agustin; Seni Oktriani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the results ofDevelopment Life Skills Through School Sports Activities. The research method used is development research from Borg and Gall which has been varied, namely (1) conducting preliminary studies, (2) model development plans, (3) initial model development, (4) revision of validation results (5) field trials small group, (6) revision of trial results (final product). The instrument used in this study used a questionnaire to measure life skills, namely thetest or LSSS Life Skills Scale for Sport(Life Skills Scale for Sport) made by Cronin & Allen (2017), which was then adapted by researchers according to research needs. The data analysis of this study used a quantitative method with descriptive statistics with assistance (SPSS). The results of the explanation above are expected to develop life skills that will help students in their daily lives, be able to have life skills to maintain positive relationships both for individuals and with others and be able to overcome any problems that come up properly and effectively through sports activities.